Adventures of an Accidental Music Librarian: Nurturing a New Library. (1st October 2020) - Nichter, Caren
ABSTRACT: In 2018, the University of Tennessee at Martin sought to expand its music degree programs, leading to the development of a satellite music library on campus. Prior to this time, the music library consisted only of a small, closed-stacks band music collection with no cataloged holdings. Due to the author's background in cataloging and her liaison role to music and fine arts, she used the band library as a foundation for expanding the music library collection. This article will discuss steps taken in the process, which may be of interest to readers for whom music cataloging is a new endeavor. Areas discussed include choice of classification for media, space considerations, funding, and the process of forming partnerships on campus.